2017
DOI: 10.1186/s12870-017-1120-5
|View full text |Cite
|
Sign up to set email alerts
|

Fine organization of genomic regions tagged to the 5S rDNA locus of the bread wheat 5B chromosome

Abstract: BackgroundThe multigene family encoding the 5S rRNA, one of the most important structurally-functional part of the large ribosomal subunit, is an obligate component of all eukaryotic genomes. 5S rDNA has long been a favored target for cytological and phylogenetic studies due to the inherent peculiarities of its structural organization, such as the tandem arrays of repetitive units and their high interspecific divergence. The complex polyploid nature of the genome of bread wheat, Triticum aestivum, and the tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 64 publications
(60 reference statements)
4
7
1
Order By: Relevance
“…Based on the deduced rRNA secondary structure ( Figure 4 ), these variants appear to be pseudogenes. Similar degraded 5S rDNA sequences have been described for many eukaryotic organisms, especially fishes ( Rebordinos et al, 2013 ; Barman et al, 2016 ), crustaceans ( Perina et al, 2011 ), and plants ( Sergeeva et al, 2017 ; Volkov et al, 2017 ). Other molecular pathways than those leading to “concerted evolution” likely contribute to shaping the landscape of plant 5S rDNA ( Nei and Rooney, 2005 ).…”
Section: Discussionsupporting
confidence: 66%
“…Based on the deduced rRNA secondary structure ( Figure 4 ), these variants appear to be pseudogenes. Similar degraded 5S rDNA sequences have been described for many eukaryotic organisms, especially fishes ( Rebordinos et al, 2013 ; Barman et al, 2016 ), crustaceans ( Perina et al, 2011 ), and plants ( Sergeeva et al, 2017 ; Volkov et al, 2017 ). Other molecular pathways than those leading to “concerted evolution” likely contribute to shaping the landscape of plant 5S rDNA ( Nei and Rooney, 2005 ).…”
Section: Discussionsupporting
confidence: 66%
“…The 5S rDNA is especially well suited for such studies, due to the smaller size of its repeat units, making the sequences technically easier to handle compared to the much larger 45S rDNA, and to the higher variability exhibited by 5S rDNA NTSs relative to those of the 45S rDNA. The 5S rDNA loci have been characterized for representatives of numerous plant taxa to reveal phylogenetic relationships ( Baker et al, 2000 ; Pan et al, 2000 ; Röser et al, 2001 ), genome evolution ( Kellogg and Appels, 1995 ; Allaby and Brown, 2001 ; Simon et al, 2018 ), and the subgenome composition of polyploids ( Kovarik et al, 2008 ; Baum and Feldman, 2010 ; Sergeeva et al, 2017 ; Volkov et al, 2017 ), natural hybrids, and artificial hybrids ( Zanke et al, 1995 ; Fulnecek et al, 2002 ; Matyácek et al, 2002 ; Volkov et al, 2007 ; Mahelka et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, gaps between contigs if they are present, tend to overlap with regions of tandem repeats. The analysis of the position of ribosomal RNA genes based on sequencing of the 5B BAC clones showed that the gap between contigs coincides with the region of tandemly repeated 5S RNA genes [ 46 ]. Thus, the distribution of short contigs along the chromosome most likely suggests that these regions are enriched for tandem repeats and vice versa, the distribution of longer regions indicates the presence of extended gene-coding regions.…”
Section: Discussionmentioning
confidence: 99%